Simulation mathematical modeling of hydroecological monitoring of water resources using space images of the Earth - Yakymchuk, Vladyslav (Scientific Centre for Aerospace Research of the Earth Institute of Geological Science National Academy of Sciences of Ukraine, Kyiv, Ukraine, 2022)
Modeling of aquatic ecosystems is the basis for solving many practical problems. These problems are related to increasing the productivity of water bodies, improving the quality of water in them and the implementation of water protection measures in catchment areas. The study is based on the integration of materials from space images of the Earth and terrestrial values of the ecological index of water quality to assess the state of aquatic ecosystems, which provides sufficient data to assess the parameters of water pollution. The issues of construction of resource-oriented scenarios of nature management based on the balance of water consumption and reproduction are considered. The role and place of mathematical modeling in the system of ecological monitoring are shown, namely that the information technology of process scenario management allows to maintain the balance of water consumption and reproduction of water resources. Integrated dynamic models of Kyiv Reservoir systems have been built, focused on establishing a balance of water consumption and reproduction. A systematic approach was used to build the models, in which the economic goals of water consumption are made dependent on the ecological state. In accordance with the principle of dynamic balance, which postulates the desire of a complex system to dynamic equilibrium with variable external forces, the creation of the method proposed a universal model of adaptive balance of the system of interdependent processes. As an example of using a systematic management methodology, consider the problem of finding a balance between the volume of water consumption and the volume of their reproduction. This balance, maintained through environmental measures, is represented by a conceptual model of the ecological and economic system. Simulation experiments with the model of adaptive balance of water resources impacts were performed. The main advantage of such computer control technologies is the wide possibility to carry out simulation experiments and choose from an ensemble of possible process scenarios that meet the target guidelines for sustainable development.